2009
DOI: 10.4314/ijbcs.v3i3.45329
|View full text |Cite
|
Sign up to set email alerts
|

Infected wound healing and antimicrobial effects of Chenopodium ambrosioides and Mitracarpus scaber

Abstract: Chenopodium ambrosioides Linn. (Chenopdiaceae) and Mitracarpus scaber Zucc. (Rubiaceae) are herbal medicinal plants. They are commonly used in Togolese folk medicine to treat skin infections such as infected wounds, dermatoses, and scabies. The aim of this work was to evaluate the wound healing and antimicrobial properties of the two plants. Firstly, we evaluated the infected wound healing property of the two plants. We induced and treated infected wound in Wistar rats as follows. We inserted a sterile needle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…C. acnes promotes NLRP3inflammasome via IL-1β release in vitro in monocytemacrophages and in vivo in mice 9 . C. acnes also stimulates the expression of tumors necrosis factor-α (TNF-α) receptors, Toll-like receptors (TLRs), interferon (IFN), matrix ISSN: 2250-1177 [20] CODEN (USA): JDDTAO metalloproteinases and interleukins (IL-1, IL-8, IL-6, IL-12) by keratinocytes, leading to inflammation and hyperkeratinisation of the pilosebaceous tissue 10 . Current research has shown that the imbalance of the fascial skin micro-organism in acne vulgaris 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. acnes promotes NLRP3inflammasome via IL-1β release in vitro in monocytemacrophages and in vivo in mice 9 . C. acnes also stimulates the expression of tumors necrosis factor-α (TNF-α) receptors, Toll-like receptors (TLRs), interferon (IFN), matrix ISSN: 2250-1177 [20] CODEN (USA): JDDTAO metalloproteinases and interleukins (IL-1, IL-8, IL-6, IL-12) by keratinocytes, leading to inflammation and hyperkeratinisation of the pilosebaceous tissue 10 . Current research has shown that the imbalance of the fascial skin micro-organism in acne vulgaris 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Aloe buettneri, Mitracarpus scaber and Hannoa undulata are used in the Togolese cosmetopoeia and to treat dermatosis. Their pharmacological studies have revealed some interesting properties that would help relieve acne sufferers: Aloe buettneri for its antioxidant and gastric antisecretory effects 16 , anti-ulcer and anti-inflammatory effects 17,18 ; Mitracarpus scaber for its antimicrobial and antiradical effects 19 , infected wound healing activities 20 and Hannoa undulata for also its antimicrobial activities 21 . In the present study, investigations were conducted on the in vitro anti-oxidant and anti-microbial activities on acne-induicing micro-organisms of Aloe buettneri, Mitracarpus scaber and Hannoa undulata.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely in Togo, the aerial parts (leaves and seeds) of Chenopodium ambrosioides are used for making herbal teas to treat several pathologies: inflammation, malaria, abdominal pain, digestive parasitosis. The plant is commonly used in traditional medicine in Togo in the treatment of abscesses and infected wounds [4].…”
Section: Introductionmentioning
confidence: 99%